Mrs. Ralph L. (Aurelia) Spaugh, 1964. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 3-8-64 p.C1.
Mrs. Ralph L. (Aurelia) Spaugh, 1964. The photo was used in an article on women who were in military service.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth